To Know and Love God : Method for Theology. - Clark, David K. (Crossway, 2010)
It is the job of all believers, not just theologians, to serve God by discerning what is true about the crucial issues of life. Our task is to learn more about God. Our privilege is to love God passionately with our minds. Clearly then, spiritual life must have theology as one of its ingredients, but this, by itself, will not guarantee a vibrant spiritual life. Rather, evangelicals must link a theological experience and an experiential theology. Knowing and loving God are both necessary.